Technical Challenges for Smooth Interaction With Seniors With Dementia: Lessons From Humanitude™ - Sumioka, Hidenobu; Shiomi, Masahiro; Honda, Miwako; Nakazawa, Atsushi (Frontiers in Robotics and AI, 2021)
Due to cognitive and socio-emotional decline and mental diseases, senior citizens, especially those with dementia (PwD), struggle to interact smoothly with their caregivers. Therefore, various care techniques have been proposed to develop good relationships with seniors. Among them, Humanitude is one promising technique that provides caregivers with useful interaction skills to improve their relationships with PwD, from four perspectives: face-to-face interaction, verbal communication, touch interaction, and helping care receivers stand up (physical interaction). Regardless of advances in elderly care techniques, since current social robots interact with seniors in the same manner as they do with younger adults, they lack several important functions. For example, Humanitude emphasizes the importance of interaction at a relatively intimate distance to facilitate communication with seniors. Unfortunately, few studies have developed an interaction model for clinical care communication. In this paper, we discuss the current challenges to develop a social robot that can smoothly interact with PwDs and overview the interaction skills used in Humanitude as well as the existing technologies.